Meniti Jejak Perbankan Syariah dari Klasik hingga Kontemporer - Hidayatullah, Muhammad Syarif (Institut Agama Islam Negeri Madura, 2020)
The sophistication of technology and the demands of different times are important factors that have an influence on interactional activities in humans as social beings, including in the economic order. The development of the times has implications for economic activities and financial products that are utilized, in response to these developments present in the Islamic economic system that has been so developed today in the midst of the people's economy, namely Islamic banking. This study aims to describe the historical flow of Islamic banking. This research is a qualitative research with a type of literature research that uses a historical approach through descriptive analysis. Functionally viewed, actually islamic banking activities consisting of funding, financing and financial service activities have been carried out from the past on a classic basis and are individualized, then tracing up to now has become a modern and institutional basis that has relevance to the modernization and advancement of information technology . In addition, the development of Islamic banks today is inseparable from the role and struggle of Muslims who care about the application of Islamic economics.[Kecanggihan teknologi dan tuntutan zaman yang berbeda menjadi faktor penting yang membawa pengaruh terhadap aktivitas interaksional pada manusia sebagai makhluk sosial termasuk dalam tatanan perekonomian. Berkembangnya zaman ikut memberikan implikasi pada aktivitas ekonomi dan produk keuangan yang dimanfaatkan, sebagai respon dari perkembangan itu hadirlah dalam sistem ekonomi syariah yang telah begitu berkembang saat ini di tengah ekonomi masyarakat yakni perbankan syariah. Penelitian ini betujuan untuk mendeskripsikan alur historis perbankan syariah. Penelitian ini adalah penelitian kualitatif dengan jenis penelitian literatur yang menggunakan pendekatan historis melalui analisis deskriptif. Dipandang secara fungsional maka sebenarnya aktivitas perbankan syariah yang terdiri dari aktivitas penghimpunan dana, pembiayaan dan jasa keuangan telah dilaksanakan sejak dulu dengan basis klasik dan bersifat individual lalu meniti jejaknya hingga sekarang telah menjadi basis modern dan bersifat institusional yang memiliki relevansi dengan modernisasi dan kemajuan teknologi informasi. Selain itu pula berkembangnya bank syariah saat ini tidak lepas dari peran dan perjuangan umat Islam yang peduli terhadap penerapan ekonomi syariah.]